2001
DOI: 10.1152/ajpgi.2001.281.2.g533
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions in gastrointestinal muscle contain multiple connexins

Abstract: In the canine gastrointestinal tract, the roles that gap junctions play in pacemaking and neurotransmission are unclear. Using antibodies to connexin (Cx)43, Cx45, and Cx40, we determined the distribution of these connexins. Cx43 was present in all locations where structural gap junctions occur. Cx40 was also widely distributed in the circular muscle of the lower esophageal sphincter (LES), stomach, and ileum. Cx45 was sparsely distributed in circular muscle of the LES. In the interstitial cells of Cajal (ICC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 43 publications
1
47
0
2
Order By: Relevance
“…Therefore, association of ICC with longitudinal muscle cells becomes important. Gap junction was rarely observed between ICC-MY and circular muscle cells, but it was absent between ICC-MY and longitudinal muscle cells (32,33); the exception was in the canine colon (34). Therefore, although the present results suggest that ICC-MY are essential for inducing NO-mediated relaxation of longitudinal muscle in the mouse ileum, functional coupling of ICC-MY and longitudinal muscle cells in the tissue requires further clarification.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, association of ICC with longitudinal muscle cells becomes important. Gap junction was rarely observed between ICC-MY and circular muscle cells, but it was absent between ICC-MY and longitudinal muscle cells (32,33); the exception was in the canine colon (34). Therefore, although the present results suggest that ICC-MY are essential for inducing NO-mediated relaxation of longitudinal muscle in the mouse ileum, functional coupling of ICC-MY and longitudinal muscle cells in the tissue requires further clarification.…”
Section: Discussionmentioning
confidence: 53%
“…63,64,[97][98][99][100] Multiple studies have also found that ICC express a variety of connexins (primarily connexin 43) which are the transmembrane proteins that assemble to form gap junctions. 73,246,247 Electrical coupling between ICC and smooth muscle was verified by physiological experiments, in which injection of currents into circular muscle cells caused electrotonic potentials in ICC-MY. 154 Park et al 160 demonstrated that Ca 2+ transients propagating through ICC-MY and smooth muscle were disrupted after the application of 18β-glycyrrhetinic acid, a gap junction uncoupler, providing functional evidence that gap junctions are involved in ICC-smooth muscle coupling.…”
Section: Gap Junctions Between Interstitial Cells Of Cajal and Smoothmentioning
confidence: 96%
“…In the present study, genes related to cell junctions were more abundantly expressed in ICC-MY than in whole tissue (Table 3). Gja1, which encodes connexin 43, is a prominent gap junction protein expressed in ICC and smooth muscle cell gap junctions in GI muscles (57). Several genes related to cell-matrix junctions and adherens junctions were also enriched in ICC-DMP (Table 4).…”
Section: Expression Of Cell Type Markers In Sorted Icc-dmp and Icc-mymentioning
confidence: 99%